2022
DOI: 10.1021/acs.joc.1c02933
|View full text |Cite
|
Sign up to set email alerts
|

Primary Amination of Ar2P(O)–H with (NH4)2CO3 as an Ammonia Source under Simple and Mild Conditions and Its Extension to the Construction of Various P–N or P–O Bonds

Abstract: A facile and efficient method for the synthesis of primary phosphinamides from Ar2P­(O)–H reagents with stable and readily available ammonium carbonate as an ammonia source is disclosed herein for the first time. This ethyl bromoacetate-mediated primary amination proceeds smoothly under mild and simple conditions, without any metal catalyst or oxidant. Moreover, this method is also appropriate for the reaction of Ar2P­(O)–H with a variety of amines, alcohols, and phenols to construct P–N or P–O bonds, with fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 62 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…Significantly, the less nucleophilic anilines also afforded 4u and 4v in moderate yields, whereas anilines were normally incompatible with the conditions of the Atherton–Todd-type reactions. 8–10 Then, several cyclic secondary amines were examined, resulting in the desired products 4w–4y in good efficiency. Notably, the phosphinylation of biologically active tryptoline, a substrate containing both an aliphatic amine and an indole, occurred selectively with the aliphatic amine.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Significantly, the less nucleophilic anilines also afforded 4u and 4v in moderate yields, whereas anilines were normally incompatible with the conditions of the Atherton–Todd-type reactions. 8–10 Then, several cyclic secondary amines were examined, resulting in the desired products 4w–4y in good efficiency. Notably, the phosphinylation of biologically active tryptoline, a substrate containing both an aliphatic amine and an indole, occurred selectively with the aliphatic amine.…”
Section: Resultsmentioning
confidence: 99%
“…7 A partial solution to this problem is the Atherton–Todd reaction, which generates phosphoryl chlorides in situ from the chlorination of P(O)–H compounds in the presence of CCl 4 /base. 8 However, a stoichiometric amount of highly toxic polyhalomethanes, Selectfluor, 8 g or unusual halides 8 h , j as the halogenating reagents is indispensable for the Atherton–Todd-type reactions (Fig. 1b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, it is worth noting that although this review primarily focuses on reactions leading to primary amines, Zhang and Zhao demonstrated the synthesis of phosphinamides through a P–H bond reaction. 55 In their work, they used ammonium carbonate as the source of ammonia, showcasing the versatility of these salts as replacements in various contexts (see Fig. 17b).…”
Section: Ammonium Saltsmentioning
confidence: 99%
“…However, the traditional Atherton–Todd reaction requires the use of highly toxic CCl 4 as the halogenating reagent and solvent (Scheme a) . Subsequently, some modified Atherton–Todd reactions using less toxic halogenating reagents (CHCl 3 , Selectfluor, Tf 2 O, or BrCH 2 COOEt) have been successively developed (Scheme b). Alternatively, catalytic Atherton–Todd-type reactions using halide catalysts (I 2 or CuCl 2 ) have been documented, but they require an excess of a strong oxidant (H 2 O 2 or K 2 S 2 O 8 ) and can be applied to only aliphatic alcohols (Scheme c).…”
mentioning
confidence: 99%